In through the out door: Biochemical mechanisms affecting flavonoid glycoside catabolism in plants. (July 2021) - Bozzo, Gale G.; Unterlander, Nicole
Highlights: Flavonol glycosides undergo degradation in developing and postharvest plant tissues. Hydrolysis of flavonol glycosides by β-glucosidases occurs in plants and microbes. Flavonol rhamnosides are likely degraded by unique α-rhamnosidases. Flavonol peroxidation is postulated to be critical for oxidative stress metabolism. Abstract: Plants are the sole source of flavonoids, a chemical category that includes flavonols. For the most part, flavonols occur as glycosides with numerous postulated biological roles in plants, including photoprotection, modulation of hormone translocation, and sequestration of reactive oxygen species. Flavonol glycosides are often considered as dead-end metabolites because related flavonoids (i.e., anthocyanins) occur in terminal tissues such as flowers and fruit, but recent evidence points to their turnover in planta, including developing photosynthetic tissues. Although microbial degradation pathways for flavonol glycosides of plant origin are well described, plant catabolic pathways are little studied by comparison. This review will address our current understanding of biochemical processes leading to the loss of flavonol glycosides in plants, with a specific emphasis on the evidence for flavonol-specific β-glucosidases. Complete elucidation of these catabolic pathways is dependent on the identification of regiospecific modifying steps, including enzymes associated with the hydrolysis of rhamnosylated flavonols, as well as flavonol peroxidation and their encoding genes. Herein, we highlight challenges for the identification of hypothetical plant α-rhamnosidases and peroxidases involved in flavonol glycoside degradation, and the potential biological role of this catabolism in mitigating oxidative stress in developing and postharvest plant tissues.